Your successful LIS career planning your career,CVs, interviews and self-promotion - Pantry, Sheila (Successful LIS professional., 1999)
This is a guide for the information professional to formulate a strategy or career plan to assist them when they apply for a new job. Using checklists, action summaries, points for reflection and outline career maps, the text offers practical advice on writing a CV and preparing for an interview.